2016
DOI: 10.1186/s40560-016-0193-9
|View full text |Cite
|
Sign up to set email alerts
|

Heat stroke with bimodal rhabdomyolysis: a case report and review of the literature

Abstract: BackgroundSevere heat stroke tends to be complicated with rhabdomyolysis, especially in patients with exertional heat stroke. Rhabdomyolysis usually occurs in the acute phase of heat stroke. We herein report a case of heat stroke in a patient who experienced bimodal rhabdomyolysis in the acute and recovery phases.Case presentationA 34-year-old male patient was found lying unconscious on the road after participating in a half marathon in the spring. It was a sunny day with a maximum temperature of 24.2 °C. His … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
(20 reference statements)
1
6
1
Order By: Relevance
“…Although rhabdomyolysis is a known complication of heat stroke, in the literature of human eWBH, this complication is not described to the same extent as we found in our animal model (Yoshizawa et al, 2016). In humans receiving eWBH, Zwischenberger et al reported a CK rise up to 1846 ± 1823 U/L 2 hr after the procedure (normal value <170 U/L), Locker et al described grade 1 (National Cancer Institute Common Toxicity Criteria) CK rise in 33% and grade 2 in 25% of the patients (time interval of occurrence of CK rise not reported) and Zablow et al also reported mild CK level increases, spontaneously recovering after 2 weeks (only measured after 3 and 14 days) (Locker et al, 2011;Zablow et al, 1997;Zwischenberger et al, 2001).…”
Section: T a B L E 2 Comparison Between Fluid Balances (Mean ± Sd) Wicontrasting
confidence: 47%
“…Although rhabdomyolysis is a known complication of heat stroke, in the literature of human eWBH, this complication is not described to the same extent as we found in our animal model (Yoshizawa et al, 2016). In humans receiving eWBH, Zwischenberger et al reported a CK rise up to 1846 ± 1823 U/L 2 hr after the procedure (normal value <170 U/L), Locker et al described grade 1 (National Cancer Institute Common Toxicity Criteria) CK rise in 33% and grade 2 in 25% of the patients (time interval of occurrence of CK rise not reported) and Zablow et al also reported mild CK level increases, spontaneously recovering after 2 weeks (only measured after 3 and 14 days) (Locker et al, 2011;Zablow et al, 1997;Zwischenberger et al, 2001).…”
Section: T a B L E 2 Comparison Between Fluid Balances (Mean ± Sd) Wicontrasting
confidence: 47%
“…is genetic variant may cause the bimodality of rhabdomyolysis during even the mildest of rehabilitation as seen in the Japanese population [9]. Accordingly, our patient has a Japanese lineage and if proven to have this genetic variant, it may have repercussions of him being an athlete in the future.…”
Section: Discussionmentioning
confidence: 72%
“…is was managed conservatively with hydration and rest from physical rehabilitation. A genetics consultation was done, and carnityl palmitoyltransferase II (CPT II) levels and phenotyping were requested (pending as of this writing) to determine genetic predisposition to rhabdomyolysis as evidenced by a bimodal rise in CPKs [9]. He was eventually discharged stable and ambulatory.…”
Section: Case Presentationmentioning
confidence: 99%
“…This has been shown to maximize EHS patients’ survival [ 5 ] and minimize organ damage from prolonged heat stress [ 21 ]. In the case studies of patients who were cooled using cooling modalities with suboptimal cooling rates (<0.15 °C·min −1 ), it was reported that patients experienced sequela (e.g., rhabdomyolysis, ischemic bowel, bilateral compartment syndrome, acute kidney injury, acute liver failure, and disseminated intravascular coagulopathy) requiring hospitalization [ 21 , 22 , 23 , 24 ]. Therefore, selection of appropriate cooling methods can dictate the outcome of EHS treatment and clinicians should recognize limitations of cooling methods other than whole-body cold-water immersion (e.g., cooling vests, ice packs, intravenous infusion, and gastric lavage) as a modality of EHS treatment.…”
Section: Discussionmentioning
confidence: 99%